Profiling of multiphosphorylated peptides in kefir and their release during simulated gastrointestinal digestion - Savastano, Maria Luisa; Liu, Yufang; Ebner, Jennifer; Dittrich, Daniel; Haus, Sabrina; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (ACS Omega, 2019)
Casein phosphopeptides are multiphosphorylated milk peptides, which can have anticariogenic activity and improve mineral absorption by binding bivalent metal ions. The present study investigated phosphopeptides in kefir, because fermentation may lead to their enhanced release from milk proteins. After selective enrichment by hydroxyapatite extraction, phosphopeptides and their phosphorylation degree were identified by MALDI-TOF-MS before and after enzymatic dephosphorylation. Peptide structures were determined by UHPLC–ESI–MS/MS revealing 27 phosphopeptides in kefir, including nine peptides containing the motif pSpSpSEE, which binds minerals most efficiently. The majority (18) of phosphopeptides derived from β-casein, but only three from the most abundant milk protein αs1-casein. After simulated gastrointestinal digestion, MALDI-TOF-MS analysis detected eight putative phosphopeptides in kefir; four of which were assigned by UHPLC–ESI–MS/MS to αs2-casein124-133, αs2-casein137-146, β-casein30-40, and κ-casein147-161. These results indicate that kefir is a good dietary source of multiphosphorylated peptide
Keywords: casein phosphopeptides; gastrointestinal digestion; kefir; MALDI-TOF-MS; pSpSpSEE; UHPLC–ESI–MS/MS